(untitled) (Modern education and development, 2025)
В народной медицине используют сок каланхоэ Перистого и каланхоэ Дегремона. Именно в нём содержится масса полезных веществ и элементов: полисахариды, дубильные вещества, органические кислоты и различные ферменты, а также магний, кремний, железо, кальций, марганец, медь и различные витамины. In folk medicine, kalanchoe Pinnate and kalanchoe Degremon juice are used. It contains a lot of useful substances and elements: polysaccharides, tannins, organic acids and various enzymes, as well as magnesium, silicon, iron, calcium, manganese, copper and various vitamins.